GREEN HYDROGEN, LOGISTICS HUBS AND REGIONAL DEVELOPMENT IN BRAZIL: AN INTEGRATIVE LITERATURE REVIEW - da Cunha, Alex Pereira (Seven Editora, 2025)
The growing relevance of green hydrogen in the context of the global energy transition has intensified debates on its economic, territorial, and institutional impacts. Beyond its role in decarbonization, green hydrogen has been associated with the reorganization of production chains and the formation of logistics hubs and corridors, with implications for regional development. This article analyzes how the structuring of these arrangements has been related to regional development in recent scientific literature, with emphasis on emerging economies and Brazil. Methodologically, an integrative literature review was conducted, guided by the PRISMA 2020 guidelines and the PCC strategy. A total of 49 studies published between 2020 and 2025 were analyzed, identified through a structured search in international and regional scientific databases. The results indicate that green hydrogen hubs can foster green reindustrialization, attract investments, and strengthen local productive capacities, provided they are associated with integrated public policies, territorial planning, and multilevel governance. However, the literature also highlights risks of energy enclaves in contexts of weak institutional coordination.DOI: https://doi.org/10.56238/sevened2025.036-134